Prevalence of Moraxella Catarrhalis as a Nasal Flora among Healthy Kindergarten Children in Bhaktapur, Nepal - Neetu Amatya; Govinda Paudel; Bhuvan Saud; Sunita Wagle; Vikram Shrestha; Bibhav Adhikari (Interdisciplinary Perspectives on Infectious Diseases)
Introduction. Moraxella catarrhalis causes mild to severe disease in all age groups, mainly in children. This study investigates the prevalence of M. catarrhalis, its cocolonization with other common nasal flora, and associated risk factors in kindergarten children in Bhaktapur. Method. A cross-sectional study was conducted among 136 healthy school-going children from four kindergartens of Bhaktapur Municipality. Nasal swabs were examined for identification and isolation of M. catarrhalis and its antibiotic susceptibility pattern. Additionally, further analysis was performed for cocolonization and associated risk factors. Results. Out of 136 students, M. catarrhalis was detected in 80 (58.8%) children. Using bivariate and multivariate analysis, the associated risk factors with significantly high carriage rates were age group of 3–4 years, classroom occupancy with 15–30 children, and antibiotic consumption within 6 months, with a p value of ≤0.05 in each of the cases. Multiple logistic regression analysis of bacterial coexistence depicted M. catarrhalis to be positively associated with Streptococcus pneumoniae and Haemophilus influenzae and negatively associated with Staphylococcus aureus. Furthermore, the highest double colonization occurred among M. catarrhalis and S. aureus and the highest triple colonization occurred among M. catarrhalis, S. aureus, and S. pneumoniae. The antibiogram pattern showed the target organisms to be highly resistant to amoxycillin/clavulanate (18.8%) and most sensitive to chloramphenicol (100%). Conclusion. This study shows a high prevalence of M. catarrhalis in healthy kindergarten children and is positively associated with other nasal isolates like S. pneumoniae and H. influenzae.